The asparagus feast - Zitner, Sheldon P. (Hugh MacLennan poetry series., 1999)
Once she woke me in the streaky dark to savour one of her delights - "larks against bells," she called it. We carried our coffees down to the minty garden and waited ankle-deep in dew. Across the shallow valley, the early traffic crept in glimmers through the groundmist. At dawn the cannonade of bells from the Certosa - as she had promised - did not drown out small songs. --from Loquacious Philomel.